2018
DOI: 10.1111/cen.13750
|View full text |Cite
|
Sign up to set email alerts
|

Are pregnancy, parity, menstruation and breastfeeding risk factors for thyroid cancer? Results from the Korea National Health and Nutrition Examination Survey, 2010‐2015

Abstract: Our findings suggest that reproductive factors can be associated with the development of thyroid cancer. A large prospective cohort study is needed to clarify the causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…In support of our results, two previous studies performed in Japan and Thailand found that thyroid cancer risk was decreased among women who had experienced pregnancy compared with those who had not [28,29]. However, many previous studies suggested that the number of pregnancies and parity could increase the risk for thyroid cancer [6,12,[30][31][32]. Additionally, some studies have suggested no significant association between the number of pregnancies and the risk of thyroid cancer [4,10,11].…”
Section: Discussionsupporting
confidence: 88%
“…In support of our results, two previous studies performed in Japan and Thailand found that thyroid cancer risk was decreased among women who had experienced pregnancy compared with those who had not [28,29]. However, many previous studies suggested that the number of pregnancies and parity could increase the risk for thyroid cancer [6,12,[30][31][32]. Additionally, some studies have suggested no significant association between the number of pregnancies and the risk of thyroid cancer [4,10,11].…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to the results of a non-Korean study in which it was verified that longer breastfeeding duration was associated with a lower prevalence of thyroid cancer [15]. The study of some female thyroid cancer patients in Korea also reported that breastfeeding period and the number of breastfeeding babies were associated with the risk of thyroid cancer [18]. A dose-response relationship between the total breastfeeding duration and the prevalence of thyroid cancer has thus been potentially confirmed in Korean women as well.…”
Section: Lower Prevalence Of Thyroid Cancer In the Longer Breastfeeding Duration Groupsupporting
confidence: 88%
“…In the case of Korean women, a trend emerged where decreasing breast cancer risk was associated with an increased duration of breastfeeding [16,17], while the total duration of breastfeeding significantly decreased the risk of thyroid cancer [18]. However, it is hard to find a study that confirms the link between breastfeeding and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dong Zhang found that the association between arti cial light at night and risk for TC was primarily driven by PTC and was more potent in women (HR, 1.81; 95% CI, 1.26-2.60) than men (HR, 1.29; 95% CI, 0.86-1.94) 6 . There is a gender difference because the occurrence of TC is closely related to estrogen 37 . Research has suggested that estrogen receptor polymorphism in TC contributed to the difference in TC incidence between men and women 11,12 .…”
Section: Discussionmentioning
confidence: 99%